Patients’ Mental Models and Adherence to Outpatient Physical Therapy Home Exercise Programs - Jon J. Rizzo; Alexandra Bell (Adult Education Research Conference, 2014)
This qualitative study identified aspects of patients’ mental models that relate to adherence to physical therapy home exercise programs. The findings may guide clinicians in designing interventions that effectively promote adherence to home exercise programs, improving patient outcomes and reducing personal and societal costs of musculoskeletal disease.